Półodwrotna Metoda w Hydrodynamice Płaskiej - S.I. Gheorghitza (Engineering Transactions)
The first part of the paper is devoted to generalization of the semi-inverse method of [1]. Some applications are given. Many boundary value problems can easily be solved for regions bounded by the curves plotted in Fig. 2 or 3 and the two radii on the real axis extending to infinity. The curves in Fig. 4 can represent boundaries for motion in channels or in porous media. Some boundary value problems for regions as shown in Fig. 5 by using the method of bipolar coordinates are dealt with in the closing part of the paper.